ANALISIS FAKTOR YANG MEMPENGARUHI INOVASI PRODUK NANOENKAPSULASI EKSTRAK PEGAGAN SEBAGAI SEDIAAN UNTUK MENGATASI SELULIT - Dewi Sondari; M. Syamsul Maarif; Yandra Arkeman (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Innovation is a research, development, and/or engineering which aims to develop thepractical application of values and context of new knowledge, or new ways to apply science andtechnology that has existed in the product or production process. Anti-cellulite innovationdevelopment based on market opportunities, goals and objectives nanoencaptulation producean anti-cellulite product using nano technology. Factors thought to influence innovation incompanies such as leadership styles, personal characteristics and dynamics of the environmentand the user market factors. In an innovation planning of nanoencaptulation should attention tothe functional aspects of a component, part of the whole system works. The main purpose offunctional analysis and design stage is to define the interaction of each component with eachother.